2006
DOI: 10.1080/17405620600605323
|View full text |Cite
|
Sign up to set email alerts
|

Eye contact and social contingency experiences from 3 to 6 months of age and their relation to the detection of non-social contingencies

Abstract: This longitudinal study focuses on the development of eye contact and the contingency of maternal reactions to infants' signals from the age of 3 to 6 months. Eighty-seven 3-month-old infants participated in this study. The amount of eye contact and of social contingencies experienced as prompt maternal responses was assessed micro-analytically based on videotaped mother -infant interactions. The ability to detect contingencies in non-social contexts was assessed by a visual expectation paradigm. The general p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…,)Dadds et al (2014),Dadds et al (2011),Daly (1978), Escher-Graub et al (1982), Francis et al (1982,Goldstein et al (1976), Gorawara-Bhat and Cook (2011), Harel et al(2011),Hore (1976),Jundi et al (2013),Kalma (1992),Keller and Zach (1993),Klusek et al (2018),Krantz et al (1983),Langer et al (2017, Langer andRodebaugh (2013),Lasalle and Conture (1991),Leeb and Rejskind (2004),Lohaus et al (2006), Lohaus et al (2001,Lutchmaya et al (2002), MacLean et al(2014),Mann et al (2012),(2013),McAdams et al (1984),Nevill (1974),Nomikou et al (2013Nomikou et al ( , 2016,…”
mentioning
confidence: 99%
“…,)Dadds et al (2014),Dadds et al (2011),Daly (1978), Escher-Graub et al (1982), Francis et al (1982,Goldstein et al (1976), Gorawara-Bhat and Cook (2011), Harel et al(2011),Hore (1976),Jundi et al (2013),Kalma (1992),Keller and Zach (1993),Klusek et al (2018),Krantz et al (1983),Langer et al (2017, Langer andRodebaugh (2013),Lasalle and Conture (1991),Leeb and Rejskind (2004),Lohaus et al (2006), Lohaus et al (2001,Lutchmaya et al (2002), MacLean et al(2014),Mann et al (2012),(2013),McAdams et al (1984),Nevill (1974),Nomikou et al (2013Nomikou et al ( , 2016,…”
mentioning
confidence: 99%
“…Among infants at risk of ASD, poor eye contact is consistently among the hallmark features later associated with a formal diagnosis (Baird et al, 2003; Jones, & Klin, 2013). Specifically, research has found that children with ASD tend to orient to the mouth region over another individual’s eyes (Klin & Jones, 2008; Klin, Shultz, & Jones, 2015), as well as orient to nonsocial stimuli in the environment that may compete for discriminated attention with the social stimuli (e.g., toys, plants, clocks; Lohaus et al, 2006; Sasson & Touchstone, 2014). A consistent environment plays a critical role in learning and developing social behaviors and therefore the role of environmental contingencies is integral to the development of eye contact among both typically and atypically developing children.…”
Section: Establishing Pivotal Infant Social Skillsmentioning
confidence: 99%